Conduction mechanisms in thermal nitride and dry gate oxides grown on 4H-SiC - Ouennoughi, Z.; Strenger, Christian; Bourouba, F.; Haeublein, Volker; Ryssel, Heiner; Frey, Lothar (Microelectronics Reliability, 2013)
The charge conduction mechanisms in Metal-Oxide-Semiconductor (MOS) capacitors formed on n-type 4H-silicon carbide (SiC) using thermally grown silicon dioxide (SiO2) as gate dielectrics are analyzed. The possible conduction mechanisms have been identified in the whole measurement range. At high electric fields, the charge conduction is dominated by Fowler-Nordheim tunneling. In addition, trap assisted tunneling and ohmic type conduction are considered to explain the cause of leakages detected at intermediate and low oxide electric fields. Various electronic parameters are extracted. The oxide breakdown strengths are higher than 8 MV/cm. Fowler-Nordheim tunneling barrier height was found to be 2.74 eV for nitride oxides and 2.54 eV for dry oxides at high electric field regions and the trap energy level extracted using trap assisted tunneling emission model was estimated to be about 0.3 eV for both oxides. The possible contribution of the Poole-Frenkel effect to the conduction mechanism was also considered, and it was found that it does not play a dominant role. © 2013 Elsevier Ltd. All rights reserved.